Factors Affecting Domestic Violence: A Qualitative Study - Rezvan Kazemi Dastjerdehei; Bahman Khosravi; Naser Iravani Manesh; Maryam Mohammadi; Mohammad Panahi Tosanloo; Hamed Sattari Bahabadi (Social Behavior Research & Health, 2020)
Background: It seems that violence is a critical issue that requires further research in order to offer new effective solutions in tune with the needs and context of the societies. The current study aimed to explore the influential factors for the incidence of domestic violence. Methods: The current research is a qualitative study conducted using content analysis. Study population included all patients admitted in the hospital to receive healthcare services. The sampling was conducted by interviewing with 50% of the hospitalized patients to assess their primary status, followed by selecting those who were found to be faced with violence. At this stage, 40 patients hospitalized as a result of domestic violence were included. Semi-structured interviews and open-ended questions were used to collect data. Results: The interviews revealed that poverty; addiction, underlying psychological disorders, delinquency, infertility of victim, family and cultural differences, inability to create emotional relationships, low educational level, low monthly income, high-risk sexual relationships, and ignoring moral codes are among the causes of domestic violence. Conclusion: It is obvious that the exact number of victims is hard to be estimated. It seems that lack of the legal, social, cultural, and economic supports results in persistence of violence creator factors at both family and society levels. It seems that performing legal solutions, strengthening social services, and paying more attention to violence creators are necessary when considering domestic violence.